Web-Based Enterprise Resource Planning (ERP) Systems Implementation Analysis at PT. Anugrah Jasa Caterindo - Nur Nafiastuti Ristianti; Eko Ganis Sukoharsono (Jurnal Ilmiah Mahasiswa FEB, 2013)
ERP systems is an information technology that is designed to integrate and automate all business processes and business functions of a company. This study is aimed at knowing the analysis of ERP implementation by using Qualitative Case Study Research in a catering industry company.  The data used in this study is primary and secondary data. For assessing the performance of ERP systems condition, the study used  descriptive case study. Descriptive analysis is used to gather or to collect in-depth information on ERP systems implemented by PT AJC. It can be concluded that there have been different opinions and responses on ERP systems performance in this company.  The  ERP systems has much supported and facilitated the operational activities of PT AJC but ERP systems has not been fully implemented by PT AJC. It is mainly implemented for its operational activities and  purposes.  As a matter of fact, the implementation of ERP systems for operational activities by PT AJC is considered good, due to the availability of the three basic elements of the system, namely: physical component, human resources, organization, or industry processes.   Keywords : ERP systems, Catering and Service Company, Case Study Analysis.